Recurrence of Mycosis Fungoides on Multiple Melanocytic Nevi: A Case Report and Review of the Literature - Valeria Brazzelli; Vincenzo Grasso; Nicolò Rivetti; Giacomo Fiandrino; Marco Lucioni; Giovanni Borroni (Karger Publishers, 2012)
Melanocytic nevi represent a widespread cutaneous finding. Nevertheless, the presence of mycosis fungoides and melanocytic nevi in the same location is an extremely rare event. We report the case of a patient affected by mycosis fungoides and treated with PUVA therapy, with complete remission of the disease. Eight years after therapy discontinuation, he presented epidermal scaling and an erythematous perinevic halo on 3 old melanocytic lesions, the clinical aspect of which was highly suggestive for Meyerson nevi. The histological and immunohistochemical examination of an excised melanocytic lesion revealed histological features consistent with the diagnosis of mycosis fungoides superimposed on junctional melanocytic nevi. The finding of patches of mycosis fungoides superimposed on melanocytic nevi is a rare event; the confounding clinical appearance with eczematous changes around a pre-existing nevus may recall the halo dermatitis known as Meyerson phenomenon; this highlights the importance of clinical and histological examination to make the correct diagnosis of dermatological diseases.